2014
DOI: 10.1111/jgh.12570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peroral endoscopic myotomy in achalasia patients with failure of prior pneumatic dilation: A prospective case–control study

Abstract: POEM is a promising therapeutic modality for achalasia patients who have failed to respond to PD therapy. Previous dilation procedures might have no obvious influence on the efficacy of POEM surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…47 This study showed a significantly longer operation time in the patients with previous pneumatic dilations; however, the outcomes in terms of the efficacy and safety were similar in both groups. 47 Another study about the learning curve of POEM also showed that previous endoscopic treatment was one of the independent predictive factors of a longer procedure time. 48 However, there were also several contrary results that showed no significant difference even in operation time, efficacy, and safety.…”
Section: Previous Endoscopic and Surgical Treatmentmentioning
confidence: 84%
“…47 This study showed a significantly longer operation time in the patients with previous pneumatic dilations; however, the outcomes in terms of the efficacy and safety were similar in both groups. 47 Another study about the learning curve of POEM also showed that previous endoscopic treatment was one of the independent predictive factors of a longer procedure time. 48 However, there were also several contrary results that showed no significant difference even in operation time, efficacy, and safety.…”
Section: Previous Endoscopic and Surgical Treatmentmentioning
confidence: 84%
“…POEM has even been performed successfully on refractory cases of achalasia following previous balloon dilation or laparoscopic Heller myotomy [52][53][54][55]. These cases should only be treated by highly experienced operators [47].…”
Section: Treatmentmentioning
confidence: 99%
“…Previous management of achalasia, including BTI, PD or LHM, does not preclude POEM [11][12][13][57][58][59][60]. In a series published by Orenstein et al [13], 40 patients received a POEM procedure, and 40% of them had had at least one prior endoscopic or surgical procedure, including nine BTI, seven PD, three both BTI and PD and three prior LHM (two with Dor fundoplication).…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%